PENINGKATAN KUALITAS PENGELOLAAN ARSIP MELALUI MANAJEMEN KEPEMIMPINAN PENDIDIKAN MODERN - Mufid Al Muttaqi, Muhammad; Fatimatuz Zahro, Arwa; Ida Nur Zufaida, Atika; Zulfa Andini, Nayli; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Archives management is a crucial aspect of an organization's administration system, serving as a center for information, evidence, and a resource for decision-making. In the modern era, marked by the rapid development of information technology, the need for a fast, accurate, and secure archives management system is increasingly pressing. Conventional archives management systems, which still rely on physical media, have various limitations, such as the risk of damage, loss, and slow information retrieval. Therefore, a more effective approach is needed, namely through the implementation of modern management. This research aims to comprehensively examine the improvement of archives management quality through the implementation of modern management. The study focuses on the basic concepts of archives management, the transformation of archival systems, the role of digital technology, and supporting and inhibiting factors for implementation. The research method used is a qualitative approach using literature studies, which examines various scientific sources such as books, journals, and regulations related to archives. The results of the study indicate that the implementation of modern management can significantly improve the quality of archives management through document digitization, the use of electronic archival systems, and increased human resource competency. Furthermore, the implementation of technology-based systems also has a positive impact on work efficiency, data security, and ease of access to information. Thus, modern management is a strategic solution to address the challenges of archives management in the digital age.